A prática docente por meio de competência e habilidade: suas implicações no processo de ensino aprendizagem de história nos anos iniciais do ensino fundamental - Rossi, Fátima Garcia Santana (2021)
This study aims to analyze the teaching practice through competence and skill and its implications in the teaching-learning process of history in the early years of elementary school. Assuming that contemporary society is inserted in a constant process of transformation, driven by new technologies, it makes it possible to identify a new pattern of society, which is focused on the production, use of information and knowledge for all age groups and social groups. Faced with this reality, educational institutions tend to reframe their role, enabling the emergence of new spaces, models and processes for the dissemination of knowledge. In this scenario, several trends and innovations appear in the educational panorama, among them, the noticeable increase in studies in the area of competence and skill in different fields and modalities of knowledge stands out. Supported in the normative and directive documents of LDB 9.394/96 (BRASIL, 1996) and BNCC (BRASIL, 2017) and in scholars such as: Zabala e Arnau (2010), Perrenoud (1999), Bittencourt (2011), Freitas (2010) and Sacristán ( 2011) among others, this study aims to understand this proposed teaching model and analyze its possibilities and limits for the teaching of history in the early years of elementary school. To this end, an educational product was developed in the form of a training tutorial for teachers in the 5th year of elementary school, from a public school in the municipal network of Aparecida de Goiânia, with the title: Understanding the teaching model through skills and skills. This tutorial aimed to promote theoretical/practical teaching input applicable in real teaching conditions through Didactic-Formative Experiment. A Didactic Sequence (DS) was also part of the research instruments, attached to this tutorial, which presented one of the possibilities for planning teaching through skills and abilities. The DS served as an instrument of illustration and evaluation. For the best development of this research and the success of its results, the following methodological procedures were adopted: (1) Bibliographic research; (2) Document analysis; (3) Field research for qualitative and quantitative exploratory analysis (4) Development and application of the Didactic-Formative Experiment. Although the teaching unit is operating through the Special Regime of Non-Presence Classes (REANP), mediated by tools and applications for online classes, this did not prevent the development of the research. It just had to undergo some adaptations in the phases and in the educational product.